The Prostate Cancer Registry: monitoring patterns and quality of care for men diagnosed with prostate cancer. (1st November 2012) - Evans, Sue M.; Millar, Jeremy L.; Wood, Julie M.; Davis, Ian D.; Bolton, Damien; Giles, Graham G.; Frydenberg, Mark; Frauman, Albert; Costello, Antony; McNeil, John J.
Abstract : What's known on the subject? and What does the study add? Operating principles exist both within Australia and internationally to provide guidance on how to establish clinical registries. In establishing a registry, consideration needs to be given to its purpose, the stakeholders and the output it will generate and to whom output will be disseminated The present study describes how a prostate cancer‐specific registry was developed that aligns with generic operating principles. We describe the governance model, the data items collected, the collection methodology clinical indicators selected for reporting and the reporting framework. OBJECTIVE: To establish a pilot population‐based clinical registry with the aim of monitoring the quality of care provided to men diagnosed with prostate cancer. PATIENTS AND METHODS: All men aged >18 years from the contributing hospitals in Victoria, Australia, who have a diagnosis of prostate cancer confirmed by histopathology report notified to the Victorian Cancer Registry are eligible for inclusion in the Prostate Cancer Registry (PCR). A literature review was undertaken aiming to identify existing quality indicators and source evidence‐based guidelines from both Australia and internationally. RESULTS: A Steering Committee was established to determine the minimum dataset, select quality indicators to be reported back to clinicians, identify the most effective recruitment strategy, and provide a governance structure for data requests; collection, analysis and reporting of data; and managing outliers. A minimum dataset comprising 72 data items is collected by the PCR, enabling ten quality indicators to be collected and reported. Outcome measures are risk adjusted according to the established National Comprehensive Cancer Network and Cancer of the Prostate Risk Assessment Score (surgery only) risk stratification model. Recruitment to the PCR occurs concurrently with mandatory notification to the state‐based Cancer Registry. The PCR adopts an opt‐out consent process to maximize recruitment. The data collection approach is standardized, using a hybrid of data linkage and manual collection, and data collection forms are electronically scanned into the PCR. A data access policy and escalation policy for mortality outliers has been developed. CONCLUSIONS: The PCR provides potential for high‐quality population‐based data to be collected and managed within a clinician‐led governance framework. This approach satisfies the requirement for health services to establish quality assessment, at the same time as providing clinically credible data to clinicians to drive practice improvement.